Zu theoretischen und praktischen Aspekten des Fachübersetzens I. - Seidl-Péch Olivia (Acta Universitatis Sapientiae: Philologica, 2016)
The question is very often discussed whether translators and translation scientists still need text corpora in translating didactic. In the last few decades text corpora enabled the use of new tools in the field of technical translation and translation research, such as the expansion of search criteria for text corpora on the Internet. The ever-recurring question of whether translators and translation scientists still need text corpora is asked at the same time.